Chemotactic TEG3 Cells’ Guiding Platforms Based on PLA Fibers Functionalized With the SDF-1α/CXCL12 Chemokine for Neural Regeneration Therapy - Castaño, Oscar; López-Mengual, Ana; Reginensi, Diego; Matamoros-Angles, Andreu; Engel, Elisabeth; del Rio, José Antonio (Frontiers in Bioengineering and Biotechnology, 2021)
Following spinal cord injury (SCI), olfactory ensheathing cell (OEC) transplantation is a promising therapeutic approach in promoting functional improvement. Some studies report that the migratory properties of OECs are compromised by inhibitory molecules and potentiated by chemical concentration differences. Here we compare the attachment, morphology, and directionality of an OEC-derived cell line, TEG3 cells, seeded on functionalized nanoscale meshes of Poly(l/dl-lactic acid) (PLA) nanofibers. The size of the nanofibers has a strong effect on TEG3 cell adhesion and migration, with the PLA nanofibers having a 950 nm diameter being the ones that show the best results. TEG3 cells are capable of adopting a bipolar morphology on 950 nm fiber surfaces, as well as a highly dynamic behaviour in migratory terms. Finally, we observe that functionalized nanofibers, with a chemical concentration increment of SDF-1α/CXCL12, strongly enhance the migratory characteristics of TEG3 cells over inhibitory substrates.